The results of overwintering (2005-2006) of Japanese persimmon (Diospyros kaki L.) in “Novokakhovske” scientific farm (Kherson region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The results of prolonged influence of low temperatures on 51 varieties of Japanese persimmon (Diospyros kaki L.) in a new introduction area as NBG-NSC scientific farm, Novaya Kakhovka, Kherson region – are reported.
Keywords: Diospiros kaki, Japanese persimmon , Kherson region.